Effect of saponin usage on physical, mechanical and fire properties of PP based wood-plastic composites - İlkay Atar (Turkish Journal of Forestry)
In this study, the effects of intumescent flame retardant and wood flour on the physical, mechanical and combustion properties of fire materials were investigated.Saponin (SP), ammonium polyphosphate (APP) and pentaerythritol (PER) were used as intumescent flame retardants.0-10% wood flour, 0-18% APP and 0-6% PER were used in production.SP was used at 0-2-4-6-8% ratio to determine the effect on the physical, mechanical and fire properties of the composite material.A total of 20 different combinations of composite materials were produced.The density value, tensile strength (TS), tensile modulus of elasticity (TM), elongation at break (EB), flexural strength (FS), flexural modulus (FM), impact strength (IS), horizontal burning and limit oxygen index (LOI) properties of the produced composites were determined.According to the test results, with the addition of wood flour, APP/PER and SP, there was a decrease in tensile strength and elongation at break values, while there was an increase in tensile modulus of elasticity, flexural strength, flexural modulus and impact strength values.An increase in the density of the samples was detected with the addition of fillers.Addition of APP/PER to composite materials improved their fire properties.In the horizontal combustion test, the flame did not progress and was extinguished in the APP/PER added samples.A decrease in burning rate and an increase in LOI value were detected with the increase in SP usage rate.